Upaya Meningkatkan Pendapatan Kelompok Ternak Lembu Rizki Melalui Branding dan Modernisasi Pengolahan Susu Pada Program Pemberdayaan Kemitraan Masyarakat - Zulaikhah, Siti Rahmawati; Sulistiyawati, Indah; Nugroho, Adityo (Universitas Mataram, 2023)
The Lembu Rizki Livestock Group is in Singasari Village, Karanglewas District, Banyumas Regency. The problems in this group are a) Low selling price of milk in cooperatives, b) Farmers do not yet have milk processing technology, c) Limited human resources, resulting in difficulties in production and marketing. The solutions offered are 1) Sales in the form of processed milk, 2) Transfer of diversification of milk processing technology in the form of pasteurized milk of various flavors and yoghurt, 3) Empowerment of family members, and marketing using digital marketing. The general objective of this Community Partnership Empowerment activity is a) to provide solutions based on situation analysis according to the needs, challenges or problems that exist in the Lembu Rizki livestock group, b) to empower the Lembu Rizki livestock group to improve their standard of living both in economic, social and cultural terms, c) transfer technology, science and art for the development of livestock groups. The results obtained from this activity are increased target knowledge and skills regarding processing milk into pasteurized milk of various flavors and yoghurt, knowing the importance of packaging and labeling for product branding, and digital marketing. Keyword: Branding, Modernization, Milk Processing, Empowerment of Community Partnerships, Livestock Groups